EXTH-15. INHIBITION OF 2-HG LEADS TO UPREGULATION OF A PRO-INFLAMMATORY GENE SIGNATURE IN A NOVEL HLA-A2/HLA-DR1 TRANSGENIC MOUSE MODEL OF IDH1R132H-EXPRESSING GLIOMA. (9th November 2020) - Chuntova, Polly; Nicolay, Brandon; Hudson, Christine; Narayanaswamy, Rohini; Ronseaux, Sebastien; Montoya, Megan; Downey, Kira; Okada, Hideho
Abstract: Recent studies have demonstrated the impacts of 2-HG on the anti-tumor immune response in isocitrate dehydrogenase (IDH)-mutant gliomas. Our laboratory has reported that mutant IDH1 (IDH1 R132H ) suppresses STAT1, the master regulator of IFN-responses and IFN-inducible chemokines, thereby contributing to the "cold" tumor environment. Our data also indicated that inhibition of 2-HG production, through the use of a small molecular inhibitor of mutant IDH, can restore anti-tumor immunity. As the IDH1 R132H mutation has been shown to elicit a CD4 + T-cell response in human leukocyte antigen (HLA)-DR1 hosts, to establish a clinically relevant mouse model of IDH1 R132H glioma, we generated a novel IDH1 R132H glioma cell line syngeneic to the HLA-A2/HLA-DR1 -transgenic mice. The cell line expresses the IDH1 R132H protein, produces ~65 µg/ml 2-HG in vitro, and forms 2-HG producing orthotopic glioma in vivo . Furthermore, ex vivo sorted tumor-associated myeloid cells (TAMCs) demonstrate high levels of intracellular 2-HG (60–80ng/1M cells), suggesting 2-HG may be taken up by these TAMCs in vivo . Treatment of tumor-bearing mice with vorasidenib, a pan-mutant IDH inhibitor, resulted in a 10-fold reduction of 2-HG levels in the tumor cells, correlate reduction in intracellular 2-HG levels in TAMCs, and 2-fold smaller tumors at time of sacrifice. Analysis of tumor tissues using the NanoString platform revealed enhanced pro-inflammatory IFN-related responses as a result of IDH1 R132H inhibition with vorasidenib. Furthermore, vorasidenib treatment increased CD4 + tumor-infiltrating T-cells coupled with upregulation of HLA-DR on tumor-infiltrating myeloid cells, suggesting the opportunity for enhanced antigen presentation. Currently ongoing studies are evaluating the benefit of combining this enhanced immune response with additional immunomodulatory treatments, such as vaccine therapy and immune checkpoint inhibition. These data represent highly translational findings as our major histocompatibility complex (MHC)-humanized model addresses current challenges in the study of IDH1 R132H -specific immunity and utilizes a clinically relevant inhibitor in phase 3 clinical development.